Dietary protein levels modulate the gut microbiome composition through fecal samples derived from lactating ewes - Liang, Jiachong; Ali, Sikandar; Lv, Chunrong; Yang, Hongyuan; Zhao, Xiaoqi; Ni, Xiaojun; Li, Chunyan; Danzeng, Baiji; Wang, Yajing; Quan, Guobo (Frontiers in Endocrinology, 2023)
In ruminants, the digestion and utilization of dietary proteins are closely linked to the bacterial populations that are present in the gastrointestinal tract. In the present study, 16S rDNA sequencing, together with a metagenomic strategy, was used to characterize the fecal bacteria of ewes in the early lactation stage after feeding with three levels of dietary proteins 8.58%, 10.34%, and 13.93%, in three different groups (H_1), (H_m) and (H_h). Based on the 16S rDNA sequencing results, three highly similar samples were selected from each group for subsequent metagenomic analysis. A total of 376,278,516 clean data-points were obtained by metagenomic sequencing. Firmicutes and Bacteroidetes were the dominant phyla in the fecal samples, regardless of the dietary protein levels. In the H_h group, the phyla Proteobacteria, Caldiserica, and Candidatus_Cryosericota were less abundant than those in the H_l group. In contrast, Lentisphaerae, Chlamydiae, and Planctomycetes were significantly more abundant in the H_h group. Some genera, such as Prevotella, Roseburia, and Firmicutes_unclassified, were less abundant in the H_h group than those in the H_l group. In contrast, Ruminococcus, Ruminococcaceae_noname, Anaerotruncus, Thermotalae, Lentisphaerae_noname, and Paraprevotella were enriched in the H_h group. The acquired microbial genes were mainly clustered into biological processes; molecular functions; cytosol; cellular components; cytoplasm; structural constituents of ribosomes; plasma membranes; translation; and catalytic activities. KEGG results demonstrated the primary involvement of these genes in the metabolism of carbohydrates, amino acids, nucleotides, and vitamins. Additionally, genes responsible for metabolism were more abundant in the H_h group than in the H_l group. 205987 genes were significantly enriched in the H_h group. In contrast, 108129 genes were more abundant in the H_l group. These differentially expressed genes mainly regulate metabolic activities. Increasing dietary protein levels enhanced ewes’ daily weight gain during the lactation stage by modulating the fecal microbiome. Investigating fecal bacterial characteristics may help researchers develop a dietary formula for lactating ewes to optimize the growth and health of ewes and lambs.